Lip‐to‐nose flap for nasal plane reconstruction in dogs: A cadaveric and in vivo feasibility study. Issue 8 (10th October 2018) - Chiti, Lavinia E.; Montinaro, Vincenzo; Lisi, Marta L. P.; Asta, Andrea G.; Marches, Silvia; Sommaruga, Paolo; Massari, Federico
Abstract: Objective: To describe a local interpolation flap based on the upper lip for the reconstruction of the dorsal aspect of the nasal plane in dogs. Study design: Ex vivo and in vivo case report. Animals: A 2‐year‐old medium‐sized spayed female mixed‐breed dog and a canine cadaver of a medium‐sized mixed‐breed dog. Methods: A dorsal defect of the nasal plane of uncertain origin in a dog was reconstructed with a unilateral interpolation flap obtained from the caudal upper lip skin and mucosa (lip‐to‐nose flap). The procedure was first performed in a cadaveric model to assess its feasibility. Results: The lip‐to‐nose flap allowed the reconstruction of a dorsal nasal plane defect with a satisfactory cosmetic outcome. The incorporation of the labial mucosa guaranteed a complete and uncomplicated wound healing of the flap; a small area of necrosis occurred at the donor site, which resolved in a few days. Conclusion: The use of a lip‐to‐nose flap was feasible in these 2 medium‐sized dogs and led to satisfactory cosmetic outcome. Clinical significance: A lip‐to‐nose flap may be considered to reconstruct dorsal nasal plane defects in dogs and allows for a cosmetic outcome.